Hadith #324 - Sahih Muslim - Abu 'Alqama أبو علقمة (Sahih Muslim)
Ibn Abbas, the son of your Prophet’s uncle, told us that the Messenger of Allah (ﷺ) had observed: On the night of my night journey I passed by Moses b. ‘Imran (peace be upon him), a man light brown in complexion, tall. well-built as if he was one of the men of the Shanu’a, and saw Jesus son of Mary as a medium-statured man with white and red complexion and crisp hair, and I was shown Malik the guardian of Fire, and Dajjal amongst the signs which were shown to me by Allah. He (the narrato
Grade: Sahih

Hadith #6004 - Sahih Muslim - Abu 'Alqama أبو علقمة (Sahih Muslim)
The son of the uncle of your Prophet (ﷺ), i. e. Ibn Abbas, reported Allah’s Messenger (ﷺ) as saying: It is not meet for a servant that he should say: I am better than Yunus b. Matta (and this Matta) is the name of his father.
Grade: Sahih